If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3 + -6x = 9x + 3 Reorder the terms: -3 + 9x + -6x = 9x + 3 Combine like terms: 9x + -6x = 3x -3 + 3x = 9x + 3 Reorder the terms: -3 + 3x = 3 + 9x Solving -3 + 3x = 3 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 3x + -9x = 3 + 9x + -9x Combine like terms: 3x + -9x = -6x -3 + -6x = 3 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -6x = 3 + 0 -3 + -6x = 3 Add '3' to each side of the equation. -3 + 3 + -6x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -6x = 3 + 3 -6x = 3 + 3 Combine like terms: 3 + 3 = 6 -6x = 6 Divide each side by '-6'. x = -1 Simplifying x = -1
| 3(r^2+r+s)= | | -12+3z=-9+32 | | 3x+y=.25 | | 50-15=5(x-1) | | 2(h+6)-h=h+2 | | 8c-4d=2s | | m^2+16m+47=6 | | 147-5x=5-7x | | -12+3z=-9+3z | | 2x+-3=-6+x | | x-4.10987279251992518266281662917361923618628=4 | | x^2+12x+22=-5 | | 20x+10=10x | | 3+4.5=4.5+3 | | 850x+1050y=78400 | | x+400000900=3 | | (ab)c=c(cb) | | 3x=2(x+4)+2 | | 10x+10=8x+16 | | x^4-x^3+3x^2=15 | | 9+0= | | 10(2x-10)=5x+10 | | 4p-5+2p=5(p-1)+p | | 31-(x+6)=6x-5 | | 7a-5b*3ab= | | 5x-20x+75=150 | | x+x+1-(x+2)=68 | | 16y^2=-7x^2+3 | | 3-(x+6)=6x-3 | | 11-y+5=-15+6y | | 4x-7x-3-9= | | 100(5x-10)=-500 |